BIMBINGAN WAWASAN KEAGAMAAN PADA ANAK USIA DINI DENGAN METODE DAKWAH DI JORONG PENINJAUAN RANAH BATAHAN PASAMAN BARAT - Rahman; Sawaluddin Siregar; Nunung Suryana Jamin; Arnes Yuli Vandika; Muhammadong (Marsialapari: Jurnal Pengabdian Kepada Masyarakat, 2024)
Providing religious teaching to young children in Jorong, the review turns out that quite a few children fail in religious practice due to a lack of providing and understanding religious insight. For this reason, it is necessary to use the da'wah method to build religious insight in young children. The methodology for implementing the service is carried out by observing every incident that occurs at Jorong Peninjauan TPA, Ranah Batahan West Pasaman. The author made direct observations of religious learning activities. This observation/observation method is intended as a way of collecting data by directly observing events or happenings in the field. The results were found in the field of guidance carried out with elders or Koran teachers, preachers and teacher educators. Namely, the application of the da'wah method to early childhood is supported by the availability of adequate facilities, high community tolerance, patience, and the example of the Da'i or teacher